O uso do método praxeológico na investigação sobre a experiência da consciência - Moreira, Victor Augusto Diniz (2024)
The present study consisted of an effort to problematize the appropriate method for investigating the experience of consciousness. And from the beginning, the task of delimiting the object of study was undertaken in order to clarify, as best as possible, what we intended to focus on. The initial motivation is to try to understand whether we can find something in the natural world that can safely support the experiences in our mental life. And so, the question was precisely to reflect on how to establish an objective justification regarding the understanding of why we have conscious experiences of the world and ourselves. From this question, the research hypothesis was inserted, which supported a conception in which the experience of consciousness is a natural aspect of human reality. It was thus possible to conceive that such human reality is guided by the scarcity of means for its full satisfaction, which in turn culminates in a dynamic system, structured in living organisms capable of autonomous conduct, essential for the conception of deliberate behavior, characterized by intentionality of our actions and the valuation of our choices. And this study can put into discussion a naturalistic notion in which consciousness would apply to minute or even catastrophic processes regarding the emergence, readjustment or forgetting of certain habitual processes that constitute the regularity of our conscious experiences. In a systematic way, through an essentially bibliographical investigation, the first chapter of this work sought to improve knowledge about the challenges that concern the nature of consciousness distributed in three central themes, namely, the difficult problem of consciousness, the problem of mind- body, and the problem of knowledge. In the second chapter, the praxeological method was brought into focus with regard to its explanatory capacity for human conduct, using different authors who, for whatever reasons, dealt with the applicability of praxeological studies, with the aim of establishing the postulates and principles on which they are based. underpins this school of thought. And in the third chapter, the aforementioned method was then used to arrive at possible considerations about what, praxeologically speaking, the experience of consciousness is. And the result of this work was to highlight that there are new questions that can be raised for discussion. That despite centuries of reflections on consciousness, there are still themes that are proposed as new and that are launched as possibilities. And it is highlighted that all academic work, no matter how much it intends to close the subject, ends up only opening new paths.